RSM22, mtYsxC and PNKD-like proteins are required for mitochondrial translation in Trypanosoma brucei - Týč, Jiří; Novotná, Lucie; Peña-Diaz, Priscilla; Maslov, Dmitri A; Lukeš, Julius (Mitochondrion, 2017)
Mitochondrial ribosomes evolved from prokaryotic ribosomes, with which they therefore share more common features than with their counterparts in the cytosol. Yet, mitochondrial ribosomes are highly diverse in structure and composition, having undergone considerable changes, including reduction of their RNA component and varying degree of acquisition of novel proteins in various phylogenetic lineages. Here, we present functional analysis of three putative mitochondrial ribosome-associated proteins (RSM22, mtYsxC and PNKD-like) in Trypanosoma brucei, originally identified by database mining. While in other systems the homologs of RSM22 are known as components of mitochondrial ribosomes, YsxC was linked with ribosomes only in bacteria. The PNKD-like protein shows similarity to a human protein, the defects of which cause PNKD (paroxysmal non-kinesigenic dyskinesia). Here we show that all three proteins are important for the growth of T. brucei. They play an important function in mitochondrial translation, as their ablation by RNAi rapidly and severely affected the de novo synthesis of mitochondrial proteins. Moreover, following the RNAi-mediated depletion of RSM22, structure of the small subunit of mitochondrial ribosome becomes severely compromised, suggesting a role of RSM22 in ribosomal assembly and/or stability.
Keywords: sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; Protozoan Proteins; LSU; YihA; Mitochondrial ribosome; Mitochondrial Proteins; Trypanosoma brucei brucei; mitochondriální proteiny; výpočetní biologie; PNKD; Gene Silencing; Computational Biology; proteosyntéza; umlčování genů; YsxC; RNA Interference; SSU; Protein Biosynthesis; RNA interference; protozoální proteiny